Szervezeti keret és szervezeti változás: egy értelmezési kísérlet (Szociológiai Szemle, 2024)
Smaller or bigger changes continuously take place in organisations. While certain changes modify the entire organisational system, others take place within the existing set or organisational conditions, often conserving the order that has evolved until then. However, it is not clear what does the concept of organisational change mean in itself, and how can its order of magnitude be interpreted. Therefore the objective of the paper is to present a possible, multi-tiered interpretation of the concept and phenomenon of organisational change. Hence the concept of organisational frame is introduced and discussed in detail, which offers a possibility also for a well-founded discussion of „first-order” and „second-order” organisational changes. However, the conscious study of the phenomenon and nature of organisational change demands the very interpretation of the meaning and operation of the organisation as well. The paper approaches the exploration of the essence of organisations from several directions, building upon the theory of logical types, on the sociotechnical systems theory, on one of the commonly known interpretations of organisational culture and on the interpretation of organisational reality as a social construction. The author does not intend to produce a comprehensive theory of the organisations and their changes, moreover, he describes these phenomena as intersubjective ones on the basis of the interpretative approaches of the theory of organisations and he shows that the dominant coalition, which possesses organisational authority, exercises fundamental influence upon the shaping and changing of organisational reality.